Globalization and the erosion of local wisdom: The crisis of traditional silk thread production in Soppeng - Tantu, Asty Munawarti (Glocal Society Journal, 2025)
This study aims to determine how globalization presents challenges to the local wisdom of silk thread production in Sabbe'ta village by analyzing the factors causing the silk thread production crisis in Sabbe'ta village. This study is a qualitative study conducted in Sabbe'ta Village, Soppeng Regency. The determination of informants in this study was carried out using a purposive technique, based on considerations of characteristics including silk thread business actors, community leaders, and village governments in Sabbe'ta village. Data collection was carried out through observation, interviews and documentation. Data analysis was carried out in stages: data collection, data reduction, data presentation, and conclusions. The results of this study indicate that the threat of globalization to local wisdom of silk activities in Sabbe'ta village has an impact on the silk thread production crisis. The main problem of the silk thread production crisis is caused by the regeneration of silkworm farmers who do not continue in silk thread production activities so that at this time the condition of local silk thread production in Sabbe'ta village continues to decline and decline. This is indicated by the factors causing the silk thread production crisis caused by the low productivity of local seeds which have an impact on dependence on imported seeds from China, then there is no regeneration to be able to continue this silk thread production activity, and the last problem is the current market price standard for cocoons which is still as low as before.